Germination of "Solo" papaya seeds treated with plant hormones - Zanotti, Rafael Fonsêca; Dias, Denise Cunha Fernandes dos Santos; Barros, Raimundo Santos; Silva, Laércio Junio da; Sekita, Marcelo Coelho (Journal of Seed Science, 2014)
The aim of this study was to investigate the effects of some plant hormones on germination of Carica papaya L. seeds of the "Solo" group taken from fruits at maturity stages 3 and 5 (50% and 75% of the fruit skin showing a yellow color). Then, the seeds were subjected to treatments involving different combinations of acid 2-chloroethylphosphonic - (CEPA 0; 5 x 10-7 and 5 x 10-4 M), GA3 (0; 10 and 50 mg / L) and KNO3 (0 or 1 M), and germination was assessed at the 14th and 30th days. Seeds from fruits at maturity stage 3 showed increased germination when treated with all growth regulators tested. KNO3 promoted a decrease in germination and in the germination speed index, especially in the seeds from stage 5. The plant hormones did not promote any increase in percentage of normal seedlings of papaya seeds. Two-Chloethylphosphonic acid (5 x 10-4 M) and the gibberellic acid applied alone in the seeds from satge 3 promoted an increase in the number of normal seedlings 14 days after sowing.

Sementes de mamão têm germinação lenta e desuniforme o que tem sido atribuído à dormência pós-colheita. Objetivou-se com o presente trabalho avaliar os efeitos de reguladores de crescimento na germinação de sementes de mamão grupo "Solo". As sementes foram extraídas de frutos nos estádios de maturação 3 e 5, que correspondem a 50% e mais que 75% da superfície externa amarela, respectivamente. Em seguida, foram submetidas a tratamentos constituidos por diferentes combinações de ácido 2-cloroetilfosfônico - CEPA (0; 5 x 10-7 e 5 x 10-4 M), GA3 (0; 10 e 50 mg / L) e KNO3 (0 ou 1 M), avaliando-se a germinação aos 14 e 30 dias. Verificou-se aumento da germinação das sementes no estádio 3 de maturação quando tratadas com os reguladores de crescimento testados. O KNO3 teve efeito negativo na germinação e no índice de velocidade de germinação, principalmente nas sementes do estádio 5. Não houve efeito dos reguladores de crescimento na porcentagem final de plântulas normais. O CEPA (5 x 10-4 M) e as giberelinas empregadas isoladamente promoveram aumento do número de plântulas normais das sementes no estádio 3, aos 14 dias após a semeadura.
Keywords: Carica papaya; CEPA; AG; Phytohormones; KNO3; Giberelina; Reguladores de crescimento